Sleep Apnea Syndrome in Type 2 Diabetic African in Benin: Prevalence and Associated Factors - AMOUSSOU-GUENOU, KOFFI DANIEL; AGBODANDE, KOUESSI ANTHELME; WANVOEGBE, FINANGNON ARMAND; GNONLONFOUN, RAPHAEL; TCHABI, YESSOUFOU; EYISSE, YASMINE; MOUSSE, LATIF (My University, 2015)
Background: Sleep Apnea Syndrome (SAS) is a public health issue because of its increasing incidence especially in type 2 diabetes, its impact on daily life quality and its complications. Objective: To determine the prevalence and clinical presentation of the SAS in type 2 diabetes in Benin. Patients and Methods: This was a cross multicenter, descriptive and analytical study which has as framework, the insulin Bank of Cotonou, the Polyclinic of Atinkanmey and the Departmental Hospital of Oueme-Plateau (CHUD-OP). The study covered six-month (March to August 2014), and included all type 2 diabetics who have given their consent for the ventilatory polygraphy. The diagnosis of Sleep Apnea Syndrome (SAS) was selected when the apnea hypopnea index (AHI) is greater than 5 per hour of sleep. Results: During the study period, 79 patients were included. Among them, 74.7% were female; the sex ratio was 0.33. The average age was 54.6 ± 9.8 years. The SAS was present in 53.2% of diabetics included. Among the diabetics who experienced an SAS, 73.8% had mild SAS, 14.3% had moderate and 11.9% had severe SAS. The SAS was predominantly obstructive (95.2%). The risk factor significantly associated with SAS was the age over 60 years (OR = 3.5 [1.3 to 9.9]; p = 0.013). Conclusion: The SAS is revealed in our black African setting to be a public health issue due to its high frequency especially in type 2 diabetic and should be considered in the evaluation of type 2 black African diabetics.
Keywords: Sleep Apnea Syndrome; Type 2 diabetes; Prevalence